The Role Played by Mitochondria in FcεRI-Dependent Mast Cell Activation - Maria A. Chelombitko; Boris V. Chernyak; Artem V. Fedorov; Roman A. Zinovkin; Roman A. Zinovkin; Ehud Razin; Lakhsmi Bhargavi Paruchuru (Frontiers in Immunology, 2020)
Mast cells play a key role in the regulation of innate and adaptive immunity and are involved in pathogenesis of many inflammatory and allergic diseases. The most studied mechanism of mast cell activation is mediated by the interaction of antigens with immunoglobulin E (IgE) and a subsequent binding with the high-affinity receptor Fc epsilon RI (FcεRI). Increasing evidences indicated that mitochondria are actively involved in the FcεRI-dependent activation of this type of cells. Here, we discuss changes in energy metabolism and mitochondrial dynamics during IgE-antigen stimulation of mast cells. We reviewed the recent data with regards to the role played by mitochondrial membrane potential, mitochondrial calcium ions (Ca2+) influx and reactive oxygen species (ROS) in mast cell FcεRI-dependent activation. Additionally, in the present review we have discussed the crucial role played by the pyruvate dehydrogenase (PDH) complex, transcription factors signal transducer and activator of transcription 3 (STAT3) and microphthalmia-associated transcription factor (MITF) in the development and function of mast cells. These two transcription factors besides their nuclear localization were also found to translocate in to the mitochondria and functions as direct modulators of mitochondrial activity. Studying the role played by mast cell mitochondria following their activation is essential for expanding our basic knowledge about mast cell physiological functions and would help to design mitochondria-targeted anti-allergic and anti-inflammatory drugs.